Optimising thermo-mechanical treatments of residual rice husk ash for cement blending - Ayman Almutlaqah; Riccardo Maddalena; Sivakumar Kulasegaram (Case Studies in Construction Materials)
Rice husk ash (RHA) is commonly considered a promising cement replacement in concrete; however, RHA obtained through uncontrolled combustion often exhibits limited pozzolanic activity due to excess unburnt carbon and a porous structure. This study investigates the effect of microstructure on the burning process for enhancing RHA properties and reducing cement content in the binder. Coarse RHA and finely ground RHA were subjected to burning at various temperatures and durations, with Particle size distribution (PSD), Scanning electron microscopy (SEM), Loss of ignition (LOI), X-ray diffraction (XRD) and fluorescence (XRF) used to investigate their properties. The pozzolanic activity index and heat of hydration were examined in mortars incorporating RHA as a cement replacement. The results demonstrated that the microstructure of RHA had a marginal effect on silica properties during the burning process, as confirmed by XRD analysis of the materials at temperatures below 800 °C. Nevertheless, noticeable variations were observed in PSD, SEM, LOI, XRF, heat of hydration, and pozzolanic activity, indicating that burning coarse RHA had more beneficial effect on combustion efficiency compared to burning finely ground RHA. This highlights the importance of an effective combustion strategy to transform residual RHA into a potent supplementary cementitious material (SCM).